Deep Submodular Optimization and LLM for Multimodal Content Extraction and Automatic Poster Generation from Long Document - Jaisankar, Vijay; Bandyopadhyay, Sambaran; Vyas, Kalp; Chaitanya, Varre Suman; Somasundaram, Shwetha (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
A poster from a long input document can be considered as a one-page easy-to-read multimodal (text and images) summary presented on a nice template with good design elements. Automatic transformation of a long document into a poster is a very less studied but challenging task. It involves content summarization of the input document followed by template generation and harmonization. In this work, we propose a novel deep submodular function which can be trained on ground truth summaries to extract multimodal content from the document and explicitly ensures good coverage, diversity and alignment of text and images. Then, we use an LLM based paraphraser and propose to generate a template with various design aspects conditioned on the input content. We show the merits of our approach through extensive automated and human evaluations.